Career self-efficacy disparities in underrepresented biomedical scientist trainees. - Deepshikha Chatterjee; Gabrielle A Jacob; Susi Sturzenegger Varvayanis; Inge Wefes; Roger Chalkley; Ana T Nogueira; Cynthia N Fuhrmann; Janani Varadarajan; Nisaan M Hubbard; Christiann H Gaines; Rebekah L Layton; Sunita Chaudhary (PLoS ONE, 2023)
The present study examines racial, ethnic, and gender disparities in career self-efficacy amongst 6077 US citizens and US naturalized graduate and postdoctoral trainees. Respondents from biomedical fields completed surveys administered by the National Institutes of Health Broadening Experiences in Scientific Training (NIH BEST) programs across 17 US institutional sites. Graduate and postdoctoral demographic and survey response data were examined to evaluate the impact of intersectional identities on trainee career self-efficacy. The study hypothesized that race, ethnicity and gender, and the relations between these identities, would impact trainee career self-efficacy. The analysis demonstrated that racial and ethnic group, gender, specific career interests (academic principal investigator vs. other careers), and seniority (junior vs. senior trainee level) were, to various degrees, all associated with trainee career self-efficacy and the effects were consistent across graduate and postdoctoral respondents. Implications for differing levels of self-efficacy are discussed, including factors and events during training that may contribute to (or undermine) career self-efficacy. The importance of mentorship for building research and career self-efficacy of trainees is discussed, especially with respect to those identifying as women and belonging to racial/ethnic populations underrepresented in biomedical sciences. The results underscore the need for change in the biomedical academic research community in order to retain a diverse biomedical workforce.